Switching Intentions in the Mobile Telecommunications Sector in Eswatini - Mazibuko, Nontsikelelo Ntombenhle (University of the Witwatersrand, Johannesburg, 2021)
This research study sought to establish factors that influence customer brand switching intention in the mobile telecoms sector in Eswatini. This was done through examining the effects that five key variables those being customer satisfaction perceived customer value, promotional activities, service quality and value-added services that literature has shown to have an effect on customer switching intention. This research study further examined the interrelationships between these variables and lastly determined how socio –economic variables impact customer switching intentions in the mobile telecoms sector in Eswatini. This research study was quantitative and used a survey method to collect primary data through an electronic questionnaire (designed on Google Forms). The population for this research study consisted of subscribers to the two mobile telecoms service providers in Eswatini and used a sample size of 342 respondents. Convenience sampling was utilised to collect data from respondents through sharing the participation invitation on Facebook. The study used a linear regression model to assess the influence of six variables; perceived customer value, value added services, promotional activities, perceived service quality, customer satisfaction and age. The model results showed that the perceived service quality, perceived customer value and customer satisfaction had a significant and positive influence on customers switching intentions. Whilst age had a negative and significant influence on customers switching intentions. The findings indicate that most respondents of the study were subscribers of the MTN network and were aged between 25-34 years, which is the youth age. Respondents reported that they did not fell valued by their network providers.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management (ENVC) Johannesburg, 2021
Keywords: Brand Switching Intention; Customer Satisfaction; Customer Retention; SDG-8: Decent work and economic growth